KUALITAS SISTEM INFORMASI, KUALITAS INFORMASI DAN PERCEIVED USEFULNESS TERHADAP KEPUASAN PENGGUNA AKHIR SOFTWARE ANALISIS KREDIT - Rizky Herawan Putra; Nila Aprila; Fenny Marietza; Madani Hatta (UNIB Press, 2020)
Influence of information system quality, information quality and perceived usefulness on end-user satisfaction credit analysis software aims is to prove the effect of information system quality on end-user satisfaction credit analysis software, to prove the effect of information quality on end user satisfaction credit analysis software, to prove the effect of perceived usefulness on end user satisfaction credit analysis software, and last to prove the effect of system quality, information quality and perceived usefulness together on end-user satisfaction credit analysis software at PT. Bank Rakyat Indonesia, Tbk Bengkulu Branch. The data analysis method used is multiple linear regression analysis. Hypothesis testing obtained results are the quality of the information system has been proven to affect the satisfaction of end users of credit analysis software at PT. Bank Rakyat Indonesia, Tbk Bengkulu Branch. This means that LAS applications can increase data processing capacity, have a high-security system, have good data correction facilities. The quality of information has been proven to affect the satisfaction of end users of credit analysis software at PT. Bank Rakyat Indonesia, Tbk Bengkulu Branch, meaning LAS software can increase user satisfaction because the credit analysis conducted can produce accurate, reliable, timely, and relevant data. And the last result is Perceived usefulness is proven to affect the satisfaction of end users of credit analysis software at PT. Bank Rakyat Indonesia, Tbk Bengkulu Branch, meaning that the LAS application is very helpful in completing the analysis quickly, the LAS application is able to increase work effectiveness and the LAS application makes it easier for employees to complete work so as to increase user satisfaction. Keywords: Information System Quality, System Quality, User Satisfaction